FOREIGN DIRECT INVESTMENT (FDI) IN RETAIL IN INDIA: RAISON DETRE OF GROWTH (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2015)
According to the Investment Commission of India, the retail sector is expected to grow almost three times its current levels to $660 billion by 2015. Investments are sought by Indian Retailers also to get necessary push for evolution of organized retailing in India, which has been much slower as compared to rest of the world. This is significant to mention that despite of the on-going wave of incessant liberalization and globalization the absence of political will to attract advanced technology and to adopt new retail format is holding retail revolution. FDI in Indian Economy is present since ages, though it is revealed from the chart that there are some states and cities where FDI inflows are larger in comparison of rest of the India. Maharashtra, Tamilnadu, Delhi, Karnataka and Andhra Pradesh are attracting two third of the total investment being the main centers of IT development in last 15 years. Moreover, on city to city basis, it is revealed that there is huge segregation in the inflows as more than 50 percent inflows are dropping in few cities Bangloru, Mumbai and National Capital Region (NCR).